PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK BERBASIS PREDICT-OBSERVE-EXPLAIN (POE) UNTUK MENUNJANG PELAKSANAAN KURIKULUM 2013 PADA MATA PELAJARAN KIMIA SMA POKOK BAHASAN KOLOID - Hairudin Hairudin '; Herdini Herdini '; Roza Linda Roza Linda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The student activities sheet (LKPD) predict-observe-explain (POE) based for chemistry subject grade XI for colloid materials based on curriculum 2013 has been developed. Method of this research is Research and Development (RnD). The research has been conducted for 5 months using a research model 4D which are Define, Design, Develop and Disseminate. The disseminate is not carried out due to takes time. The instruments of this research are questioners which are given to the validators. There are four validators, three validators are lecturer of chemistry riau university and one validator is teacher SMA 12 Pekanbaru. The result of this research shows the validity of student participant exercise sheet (LKPD) us 90,2 %, that the category is valid. Based on the result analysis can be concluded that the learning device consist of student activities sheet (LKPD) predict-observe-explain (POE) based which is developed for the chemical learning device subject of grade XI for colloid materials valid or proper based on the curriculum 2013.Keywords: Student participant exercise sheet (LKPD), predict-observe-explain(POE), Curriculum 2013, Colloid